Influence of online comments on clothing impulse buying behavior in mobile short video app live broadcast - Hewei, Tian (Frontiers in Psychology, 2022)
Based on elaboration likelihood model (ELM), this paper introduces the central route and peripheral route of online comments and constructs a conceptual model affecting consumers’ clothing impulse buying behavior in live broadcast. A total of 737 questionnaires were collected, and 709 valid questionnaires were used for questionnaire analysis. According to the ELM, there are central route (comment quality and comment comprehensiveness) and peripheral route (comment quantity and commentator credibility) of online comments. The results show that in addition to the commentator credibility, the comment quality, comment comprehensiveness, and comment quantity have a significant positive impact on impulse buying behavior. Fashion involvement plays a moderating role in the relationship between online comments and impulse buying behavior. This paper will provide theoretical support for live broadcast clothing marketing and provide suggestions for the development and design of live broadcast.